2017
DOI: 10.14348/molcells.2017.2320
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Protein Tyrosine Phosphatase 1B Inhibition against ER Stress-Induced Toxicity

Abstract: Several lines of evidence suggest that endoplasmic reticulum (ER) stress plays a critical role in the pathogenesis of many neurodegenerative diseases such as Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. Protein tyrosine phosphatase 1B (PTP1B) is known to regulate the ER stress signaling pathway, but its role in neuronal systems in terms of ER stress remains largely unknown. Here, we showed that rotenone-induced toxicity in human neuroblastoma cell lines and mouse primary cortica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 53 publications
(58 reference statements)
1
17
0
Order By: Relevance
“…Recent studies have shown that extensive involvement of ER stress in microglial activation causes cerebral injuries in Alzheimer’s disease [ 47 ], spinal cord injuries [ 48 ], and LPS/cocaine-induced neuroinflammation [ 17 , 49 ], and PTP1B has been reported to promote ER stress [ 15 , 16 ]. In the current study, increased PTP1B expression in the ipsilateral cortex was synchronous with the activation of UPR after IR injury [ 24 ], and intracerebroventricular administration of PTP1B inhibitor significantly attenuated IR injury-induced overall ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that extensive involvement of ER stress in microglial activation causes cerebral injuries in Alzheimer’s disease [ 47 ], spinal cord injuries [ 48 ], and LPS/cocaine-induced neuroinflammation [ 17 , 49 ], and PTP1B has been reported to promote ER stress [ 15 , 16 ]. In the current study, increased PTP1B expression in the ipsilateral cortex was synchronous with the activation of UPR after IR injury [ 24 ], and intracerebroventricular administration of PTP1B inhibitor significantly attenuated IR injury-induced overall ER stress.…”
Section: Discussionmentioning
confidence: 99%
“…LPS-induced neuroinflammation in microglia is also mitigated by PTP1B inhibition [25]. In addition, a recent study indicated that ER stress-induced neuronal toxicity is dramatically reduced by PTP1B inhibition in Drosophila and mammalian neurons [26]. However, it has never been determined whether PTP1B is implicated in the proinflammatory activation of astrocytes.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, mitochondria may also have effects on ER stress. Studies showed that the mitochondria and ER stress has crosstalk in many models (Malhotra and Kaufman, 2011 ; Senft and Ronai, 2015 ), and the block of respiratory chain complex with rotenone or antimycin A that leads to mitochondrial dysfunction exerts great effects on ER stress (Lee et al, 2010 ; Jeon et al, 2017 ; Heo et al, 2019 ). Further studies are needed to investigate the effects of mitochondria to ER stress regarding Homer1 protein regulation.…”
Section: Discussionmentioning
confidence: 99%